Faktor-faktor yang Memengaruhi Minat Petani Terhadap Pemasaran Digital Bunga Krisan di Kecamatan Bandungan, Kabupaten Semarang - Fransisca, Ferra; Setiadi, Agus; Mariyono, Joko (Universitas Galuh, 2025)
The dependence of chrysanthemum farmers on conventional marketing is one of the causes of fluctuations in chrysanthemums sales. Chrysanthemum farmers in Bandungan Sub-District are generally uninterested in digital marketing. According to the Unified Theory of Acceptance and Use of Technology (UTAUT) model, factors influencing farmer’s intention and behavior toward technology include performance expectancy, effort expectancy, social influence, and facilitating conditions. This study aims to analyze factors influencing farmer’s interest in digital marketing of chrysanthemum in Bandungan Sub-District, Semarang Regency. The study was conducted from March to April 2025 in Candi and Kenteng Villages, Bandungan Sub-District, Semarang Regency. The research method used a survey method. The sampling method used purposive sampling method with 100 respondents. The data used was primary and secondary data. Data collection was done by interviews, observation, and documentation. The data was analyzed using descriptive analysis and multiple linear regression analysis. The results showed that the coefficient of determination (R²) was 0.729, which means that the variables used in this study were able to explain 72.9% of farmer’s interest in digital marketing, while the other 27.1% were explained by variables that were not included in this study. The F-test showed that the variables had a significant simultaneous effect on farmer’s interest. The t-test showed that performance expectancy, effort expectancy, and facilitating conditions have a significant effect on farmer’s interest, while social influence has no significant effect. Therefore, awareness of benefits of digital marketing and increasing the role of influential people is needed to increase farmer’s interest.